MENINGKATKAN AKTIVITAS DAN KETERAMPILAN BERPIKIR KRITIS MENGGUNAKAN MODEL MAGIC DENGAN PERMAINAN CITIZENSHIP MATCH MASTER SDN TELUK DALAM 1 - Risda; Diani Ayu Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this research is the low level of activity and critical thinking skills student. This is due to the lack of use of varied learning models and media and students not being able to solve problems. Efforts to overcome this are by using the MAGIC model and the Citizenship Match Master game. The aim of this research is to analyze increases in student activity and critical thinking skills. This research uses the type of Classroom Action Research (PTK). The research subjects were 20 students of the VA class at SDN Teluk Dalam 1 Banjarmasin. The research results showed that student activity at meetings 1 to 4 increased from 35% with criteria